Quantitative evaluation of pore characteristics of sodic soils reclaimed by flue gas desulphurization gypsum using X‐ray computed tomography. (29th January 2020) - Liao, Renkuan; Yu, Haoliang; Yang, Peiling; Lin, Henry
Abstract: Flue gas desulphurization (FGD) gypsum can effectively remediate sodic soils through improving two‐dimensional/three‐dimensional (3D) soil pore characteristics, especially vertical macroporosity. Understanding the response pattern of pore characteristics of sodic soils with different textures to FGD gypsum reclamation measures is critical to formulating appropriate improvement strategies for addressing growing challenges of land degradation. The objectives of this study were (a) to quantify the effect of FGD gypsum on two‐dimensional/three‐dimensional pore characteristics of amended sodic soils using X‐ray computed tomography (CT); and (b) to investigate the response pattern of different sodic soils to reclamation measures. Three types of intact sodic soils (sandy loam, silty loam, and silt soil) were collected from different sodic fields in north China for X‐ray CT image scan, and soil pore characteristic parameters (including porosity, pore network density, pore length density, and tortuosity) were measured. The results indicate that the high proportion of horizontal pores and lower pore length density are typical features in the sodic soils investigated. The responses of three sodic soils to reclamation measures demonstrate obvious variations that the 3D macroporosity of silt sodic soils was significantly increased ( p < .05) by 53.7%, showing more sensitive and better effect than that of sandy loam (52.9%) and silty loam (20%) sodic soils, in which the reclamation improved the vertical macroporosity of silt sodic soil by 164.6%. It is speculated that the higher clay and silt contents in the silt sodic soils and their interaction with gypsum contribute to the expansion of pore size, and the formed macropore promotes the vertical migration of clay and silt particles to further increase the vertical macroporosity. In addition, FGD gypsum is beneficial for the formation of new pores in silt loam soils. The findings of this study confirm the feasibility of quantifying pore characteristics of sodic soils with the help of X‐ray CT images and suggest that it is necessary to adopt specific reclamation strategies for different degraded sodic soils.